A global estimate of terrestrial net secondary production of primary consumers. Issue 12 (17th September 2019) - Street, Garrett M.; McNickle, Gordon G.
Abstract: Aim: Net secondary production (NSP) emerges from the consumption of net primary production (NPP) by all heterotrophic organisms. There has been sporadic interest in the importance of NSP, but no global estimates have been produced. Here, we examine NSP and attempt a global estimate using contemporary NPP data combined with modern metabolic scaling theory for consumption rates. We distinguish between potential NSP, as the amount of secondary production that could be supported by NPP, and realized NSP, as the amount remaining after anthropogenic habitat disruption. Location: Global. Time period: 2000–2014. Methods: We present a metabolic model of NSP, implementing a type II functional response for consumption rates, wherein search efficiency and handling time are calculated based on consumer mass and ambient temperature. We solve this model for each 0.05‐decimal‐degree pixel in the global terrestrial biosphere, using as data inputs NPP (MOD17A3) and land‐surface temperature (MOD11C3). We aggregate estimates within global land‐cover classifications (MCD12C1) to obtain cover‐specific and global estimates of NSP. We also correct our estimates based on declines in consumer abundance reported in Living planet report 2014 . Results: We estimate that potential NSP is 4.74 Pg C/year globally (95% CI: 3.75–5.75). When we correct for global consumer population declines, realized NSP is estimated at 2.37 Pg C/year (95% CI: 1.86–2.89), a loss of 50% in the rate of carbon flux through secondary consumers. Main conclusions: Our estimates should not be viewed as the last word on NSP but are sufficient to suggest that the flux of carbon through consumers is of a similar magnitude to many other fluxes crucial to the global carbon cycle. We view this as a hypothesis to be tested that suggests NSP deserves significantly more attention in Earth systems, macroecology and biogeochemical research.